Slit2 Protects Hearts Against Ischemia-Reperfusion Injury by Inhibiting Inflammatory Responses and Maintaining Myofilament Contractile Properties - Li, Xiang; Zheng, Shuang; Tan, Weijiang; Chen, Hongqi; Li, Xiaohui; Wu, Jian; Luo, Ting; Ren, Xuecong; Pyle, W. Glen; Wang, Lijing; Backx, Peter H.; Huang, Ren; et al. (Frontiers in Physiology, 2020)
Background The axon guidance cue Slit2 recently has been found to regulate calcium homeostasis and molecular signaling in various stress events in different organs. However, whether Slit2 plays a role in cardiac ischemia-reperfusion (IR) injury has not been reported. Here, we aimed to investigate the role of Slit2 and the underlying mechanisms in cardiac IR injury. Methods Langendorff-perfused isolated hearts from Slit2-overexpressing (Slit2-Tg) mice and their background strain C57BL/6J mice were subjected to 20 min of global ischemia followed by 40 min of reperfusion. Left ventricular function of isolated hearts was monitored. Infarct size of post-IR hearts was determined by staining with 2,3,5-triphenyltetrazolium chloride (TTC) and histological changes of cardiac tissues and cells were determined with hematoxylin-eosin (HE) staining and transmission electron microscopy. Transcriptomic analysis was used to predict the biological processes and signaling pathways affected by Slit2 overexpression in the post-IR myocardium. Pro-Q staining and Western blotting was used to assess the phosphorylation levels of cardiac myofilaments and expression levels of myofilament-associated protein kinase and phosphatases. Results Slit2 overexpression increased post-IR left ventricular developed pressure (LVDP) by 35% and reduced infarct size by 53%, along with decreased myofibrillar disruption, mitochondrial swelling, and mitochondrial cristae dissolution. Slit2 overexpression significantly changed post-IR gene expression profiles. Functional products of these genes include regulation of cation transmembrane transport, cation homeostasis, collagen fibril organization, and regulation of heart rate. And post-IR myocardial KEGG pathways upregulated by Slit2 overexpression include ECM-receptor interaction, PI3K-Akt signaling pathway, and adrenergic signaling. Slit2 overexpression impacted myofilament phosphorylation together with myofilament-associated protein kinase C (PKC) isoforms and protein phosphatases (PPs). IR in C57BL/6J hearts upregulated phosphorylation of cardiac troponin-I (cTnI), which was suppressed by Slit2 overexpression. Myofilament-associated PKCε, PKCδ, and PP2A were significantly increased post-IR in C57BL/6J hearts, but in Slit2-Tg hearts, myofilament-associated PKCε and PP2A were increased and PKCδ was suppressed. Conclusions Our results demonstrate that Slit2 overexpression protects cardiac function and reduces IR injury, which is associated with Slit2-induced gene profile shifts. The suppression of MyBP-C and troponin-I phosphorylation, and myofilament-associated PKCδ levels induced by Slit2 overexpression could contribute to the cardioprotection of Slit2 in post-IR myocardium.